Enhancing Diagnostic Precision and Treatment Guidance in Ovarian Neoplasms: Evaluating Immunohistochemistry's Role and Utility - Javaid, Parsa; Naz, Asima (Indus Journal of Bioscience Research, 2025)
Background: Ovarian neoplasms are a heterogeneous group of tumors with varied histogenesis and biological behavior. Accurate classification of these tumors is critical for appropriate clinical management. However, relying solely on hematoxylin and eosin (H&E) staining can lead to diagnostic uncertainty, particularly in borderline and poorly differentiated tumors. Immunohistochemistry (IHC) offers an adjunct diagnostic modality by identifying cell-specific markers that enhance diagnostic precision. Objective: To evaluate the utility of immunohistochemistry as an adjunct to H&E staining in the classification of ovarian neoplasms and to assess the level of diagnostic concordance between the two methods. Material and Methods: This descriptive cross-sectional study was conducted at the Department of Histopathology, Fatima Jinnah Medical University, Lahore from January 15, 2025 to April 14, 2025. A total of 100 archived cases of histologically confirmed ovarian neoplasms were included. Initial diagnoses based on H&E-stained sections were compared with final diagnoses incorporating IHC markers such as CK7, CK20, WT1, Inhibin, p53, and others. Data were analyzed using SPSS version 25. Kappa statistics and Chi-square tests were applied. Results: Of the 100 cases, 89 (89.0%) showed concordance between H&E and IHC diagnoses. The Kappa coefficient was 0.820 (p < 0.001), indicating almost perfect agreement. No statistically significant association was observed between diagnostic agreement and menopausal status (p = 0.803), family history (p = 0.668), or tumor type (p = 0.243). Conclusion: IHC significantly enhances diagnostic accuracy in ovarian neoplasms and should be considered a standard adjunct to conventional histopathology, regardless of patient demographics or tumor subtype.